Scaling applications with irregular memory access on Blue Gene/P and Lomonosov supercomputers using the extended SHMEM+ library - Korzh, A.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2010)
An extension of SHMEM library with original synchronization schemes and active messages is considered. The new library is called SHMEM+. The basic SHMEM library and the programming style imposed by it are described. The modification details of the OpenMP NPB UA benchmark version for the SHMEM and SHMEM+ libraries implemented by the author for the Blue Gene/P and Lomonosov supercomputers are discussed.